Media aspects of the cultural heritage of St. Petersburg in the branding of creative spaces - Lyudmila P. Maryina; Daria A. Amelicheva (Управление культурой)
The article discusses the branding strategies of creative clusters in St. Petersburg on the example of "Sevkabel Port", "New Holland" and "Islands of Forts" in the context of the development of creative tourism. This allows us to trace the transformation of the brand of creative spaces in St. Petersburg and determine the place of cultural heritage in dynamic processes.To fully cover the theme of the creative spaces tourism brand, it is worth noting the fact that in Russia the creators of creative spaces do not adhere to a single name, using different concepts: “space”, “creative space”, “creative space”, “art space”, “ art center”, “creative cluster” and “art cluster”.This context determines the subject-object discourse of our scientific discourse. The object of study in this article is media resources that promote the tourism brand of the following creative spaces in St. Petersburg: "Island of Forts", "New Holland", "Sevkabel Port". The subject of the study is the specificity of the transformation of the tourist brand of creative spaces of St. Petersburg into the media under the influence of the cluster belonging to the cultural heritage factor.